Digitalisation and workers wellbeing: The impact of digital technologies on work-related psychosocial risks - Ignacio González Vázquez; Maurizio Curtarelli; Ioannis Anyfantis; Emmanuelle Brun; Annick Starren (European Commission, Joint Research Centre (JRC), 2024)
This paper examines the psychosocial risks associated with the digital transformation of work, focusing on the automation of tasks, digitalisation of work processes, and the platformisation of work. It highlights that while automation and digitalisation can offer ergonomic and occupational safety and health benefits, they may also diminish worker autonomy and increase mental health risks. The adoption of digital technologies can improve communication and engagement but may lead to intensified workloads and can incentivise an 'always-on' culture. Platform work, with its precarious employment conditions, can also exacerbate occupational safety and health risks. The paper also argues that the spread of platform-like worker monitoring and algorithmic management to traditional workplaces can exacerbate certain psychosocial risks. The paper confirms that addressing these challenges requires a comprehensive approach that includes worker consultation, integration of OSH considerations from the design phase, and a holistic risk assessment that considers both technological and organisational contexts.
Keywords: 330; digitalisation; psychosocial risks; occupational safety and health